Benzo[a]pyrene exposure under future ocean acidification scenarios weakens the immune responses of blood clam, Tegillarca granosa. Issue 63 (April 2017) - Su, Wenhao; Zha, Shanjie; Wang, Yichen; Shi, Wei; Xiao, Guoqiang; Chai, Xueliang; Wu, Hongxi; Liu, Guangxu
Abstract: Persistent organic pollutants (POPs) are known to converge into the ocean and accumulate in the sediment, posing great threats to marine organisms such as the sessile bottom burrowing bivalves. However, the immune toxicity of POPs, such as B[a]P, under future ocean acidification scenarios remains poorly understood to date. Therefore, in the present study, the impacts of B[a]P exposure on the immune responses of a bivalve species, Tegillarca granosa, under present and future ocean acidification scenarios were investigated. Results obtained revealed an increased immune toxicity of B[a]P under future ocean acidification scenarios in terms of reduced THC, altered haemocyte composition, and hampered phagocytosis, which may attribute to the synergetic effects of B[a]P and ocean acidification. In addition, the gene expressions of pathogen pattern recognition receptors (TLR1, TLR2, TLR4, TLR6), pathway mediators (TRAF6, TAK1, TAB2, IKKα and Myd88), and effectors (NF-ĸB) of the important immune related pathways were significantly down-regulated upon exposure to B[a]P under future ocean acidification scenarios. Results of the present study suggested an increased immune toxicity of B[a]P under future ocean acidification scenarios, which will significantly hamper the immune responses of T. granosa and subsequently render individuals more susceptible to pathogens challenges. Graphical abstract: Highlights: Increased immune toxicity of B[a]P under future ocean acidification scenarios. Synergetic effects of B[a]P and OA on THC, haemocyte composition, phagocytosis. B[a]P under future OA scenarios down-regulated expression of immune related genes.